Mesenchymal stem cells in asthma - AKKOÇ, TUNÇ (Springer, 2020)
Asthma is one of the worldwide respiratory health problem that affect children and adult. Current treatment strategies such as conventional and allergen immunotherapy still fall behind. Mesenchymal stem cells (MSCs) have wide regenerative capacity and immunoregulatory activity with their wide range of secretions and contact dependent manner. In this review, we focus on the current treatment strategies for asthma and MSCs as a new therapeutic tool. © Springer Nature Switzerland AG 2019.
Keywords: Asthma; Mesenchymal stem cells; İmmunoregulation; İmmunotherapy